Evaluating earthquake-induced damage in Dogansehir, Malatya after 2023 Kahramanmaras Earthquake sequence: Geotechnical and structural perspectives - Dedeoglu, Ibrahim O.; Yetkin, Musa; Tunc, Gulen; Ozbulut, Osman E. (Elsevier, 2025)
On February 6, 2023, two major earthquakes with magnitudes Mw = 7.7 and Mw = 7.6 struck southeastern Turkiye, causing catastrophic damage and loss of life across 11 provinces, including Malatya. This study focuses on documenting the geotechnical observations and structural damage in Dogansehir, one of the hardest-hit districts not only in Malatya but in the entire affected region. An overview of the-region's tectonic and geological background is presented, followed by an analysis of ground motion data specific to Malatya. A detailed examination of seismic data from stations near Dogansehir was provided to better understand the seismic demands during the earthquakes. The paper then provides insights into the geotechnical conditions, building characteristics, and a damage ratio map of Dogansehir. The influence of local tectonics and geology on the observed damage is analyzed, alongside an evaluation of the seismic performance of masonry and reinforced concrete structures. Dogansehir, located near the epicenters of the Kahramanmaras earthquakes, suffered major structural damage. This was due to the surface rupture occurring near the settlement areas, the establishment of the district centre on the alluvial soil layer and the deficiencies/errors in the building systems. Building settlements on or near active fault zones, as well as on soft soil, leads to serious consequences and should be avoided or require special precautions.
Keywords: Kahramanmaras earthquakes; Tectonic; Surface rupture; Field investigation; Earthquake damage; Reinforced concrete buildings; Masonry buildings